Conception and viable twin pregnancy in a patient with metastatic melanoma while treated with CTLA-4 and PD-1 checkpoint inhibition. Issue 4 (August 2020) - Bucheit, Amanda D.; Hardy, John T.; Szender, J. Brian; Glitza Oliva, Isabella C.
Abstract : The treatment of cancer during pregnancy presents a unique challenge. Optimal treatments are often altered or even delayed to protect fetal growth and organogenesis. The landscape of cancer treatment has shifted dramatically over the past several years and treatment with checkpoint inhibitors, including anti-PD1 and anti-CTLA-4 agents has revolutionized treatment outcomes for patients across numerous tumor types. Until recently, little is known about the use of checkpoint inhibitor therapy during pregnancy; however, in animal studies, exposure to checkpoint inhibitors at the time of or after conception led to high incidences of spontaneous abortion, stillbirth, and premature delivery. In this report, we describe the successful pregnancy and clinical course of a patient diagnosed with metastatic melanoma who conceived twins while undergoing dual checkpoint blockade with ipilumumab and nivolumab. While there are case reports of patients receiving checkpoint inhibitors during pregnancy, our case is the first to describe a successful pregnancy that was conceived during treatment with combination anti-CTLA-4 and PD-1, with therapy continuing throughout pregnancy. This case adds to the growing evidence that favorable pregnancy outcomes may be possible while receiving checkpoint inhibition, which will hopefully allow for more optimal treatment of young pregnant patients with cancer.